Efektivitas Penggunaan Worksheet R Dalam Pembelajaran Teori Probabilitas - Joko Sungkono; Andhika Ayu Wulandari (Absis: Mathematics Education Journal, 2021)
Experiments that are often used to understand the theory of probability include the toss of currency, rolling of the dice, taking the ball randomly from a box, and drawing a bridge card. If this series of experiments is carried out several times, identifying possible samples produced is not an easy task. Learning probability theory material requires a new breakthrough in order to make it easier for students to understand according to their era. This research applies the use of R-based student worksheets (R worksheets) in learning probability theory. This paper discusses the effectiveness of using the R worksheet in learning probability theory. This research involved the experimental class and the control class. The experimental class used students in the Mathematics Statistics I course for Mathematics Education Study Program, Widya Dharma University, Klaten, while the control class used students in the Mathematics Statistics I course for Mathematics Education Study Program, Bangun Nusantara University, Sukoharjo. The experimental class used the R worksheet with R software-based learning, while the control class used the conventional method. From the pre-test result data, it is known that the 2 sample classes have the same initial ability. Based on the data analysis of the post-test scores, it is known that the experimental class scores are better than the control class. This means that the use of the R worksheet is effective in learning probability theory.